Ishiharaite, (Cu,Ga,Fe,In,Zn)S, a new mineral from the Capillitas mine, Northwestern Argentina - Marquez Zavalia, Maria Florencia (2014)
Ishiharaite is a new sulfide mineral, (Cu,Ga,Fe,In,Zn)S, discovered at the Nueva Esperanza vein, Capillitas mine (27°20′43″ S, 66°23′17″ W, 3290 m osl) an epithermal ore deposit belonging to the Farallón Negro Mining District, northwestern Argentina. The mineral occurs as subhedral, equidimensional, individual grains (20 to 50 μm in size) included in tennantite. It is a dark gray metallic mineral, opaque and non-fluorescent. Under polarizing-reflected light, it is an isotropic mineral, and its color is burgundy brown with a faint violet hue in air and violet-burgundy in oil. The main reflectance values are (Rair,Roil - Λ/nm): 18.27, 6.77 - 470; 20.10,7.91 - 546; 21.74,8.96 - 589; and 23.94,10.44 - 650. Ishiharaite is cubic, space group F4¯3m, a 5.368(1) Å, V 154.68(1) Å3, Z = 4. The strongest five X-ray powder-diffraction lines [d in Å (I)(hkl)] are: 3.096 (100) (111); 1.897 (60) (220); 1.620 (40) (311); 2.684 (20) (200); 1.097 (15) (422). Electron-microprobe analyses of the natural grains (n = 22) give an average composition (wt.%) of: S 30.77, Cu 33.61, Ga 13.31, In 9.48, Zn 5.74, Fe 6.13; the average (n = 6) chemical composition of the synthetic phase is: S 30.73, Cu 28.05, Ga 15.99, In 11.86, Zn 7.37, Fe 6.13. The empirical formulae of ishiharaite and the synthetic analogue, based on 2 apfu, are: (Cu0.55Ga0.19Fe0.13In0.08Zn0.08)Σ1.03S0.97, and (Cu0.45Ga0.24Fe0.11In0.11Zn0.11)Σ1.02S0.98, respectively. The mineral (IMA No. 2013-119) is named in honor of Dr. Shunso Ishihara (b. 1934), Emeritus Advisor of AIST (Advanced Industrial Science and Technology), Tsukuba, Japan.